Evolusi Pemikiran Ekonomi Islam: dari Era Klasik Hingga Era Kontemporer - Nurul Aini Harahap; Suci Indah Triani; Kurnia Fitri; Ahmad Wahyudi Zein (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the evolution of Islamic economic thought from its classical roots to contemporary interpretations, highlighting significant paradigm shifts and the contributions of influential figures throughout its history. During the classical era, Islamic economic thought drew heavily from the teachings of the Qur'an and Hadith, as interpreted by scholars such as Abu Yusuf, al-Ghazali, and Ibn Khaldun. At the heart of this thinking are the principles of social justice, the prohibition of usury, and the need for a fair distribution of wealth. Recently, there have been important updates in Islamic economic thought, shaped by the global socio-economic context and the imperative to address modern economic problems. Key figures such as Muhammad Baqir al-Sadr and Umar Chapra have played an important role in developing a more relevant Islamic economic theory, combining concepts such as Islamic banking, macroeconomics, and entrepreneurship based on Islamic ethics.